RELIGIOUS MODERATION AMONG INDIGENT FAMILIES IN JAKARTA - Nurul Qolbi Izazy (Balai Penelitian dan Pengembangan Agama Jakarta, 2022)
Intolerance in society can be prevented by increasing religious moderation. As a city representing Indonesia's plurality, Jakarta has poverty problems. At the same time, poverty is one of the triggering factors for acts of radicalism and intolerance. This study aims to analyze the concept of religious moderation in indigent families in Jakarta. This research was conducted with a descriptive qualitative approach. The informants of this research are the Beneficiary Families of the Family Hope Program (KPM PKH). The study results reveal that indigent families (KPM PKH) are still not familiar with the word religious moderation. Although in their daily attitude, they often reflect a moderate attitude. This ignorance is caused by a lack of information related to religious moderation and low religious literacy skills.